Book of Wisdom - Osho (Pune, 2001)
Osho is known around the world for his pioneering contribution to meditation $1 (Bthe science of inner transformation $1 (Bwith the unique approach of his "Osho Active Meditations" acknowledging the accelerated pace of the contemporary world and bringing meditation into modern life. Based on the Seven Points of Mind Training by the 11th-century Buddhist mystic Atisa, The Book of Wisdom removes the dust of tradition that has gathered around meditation, conveying the essential science and methodology of the practice with a freshness and spontaneity that is rarely found in contemporary spiritual works. The book is a guide for inner discipline and transformation that is also highly accessible, incorporating light, often humorous question-and-answer sessions between the author and his audience that help readers make the practical connection between spiritual theory and meditation as a lifestyle.s
Keywords: Meditation